Efektivitas Pemberian Kompos dalam Meningkatkan Produktivitas Padi MSP pada Sistem Tanam Jajar Legowo 2:1 - Nyang Vania Ayuningtyas Harini; Yeyen Ilmiasari; Elida Yantama (Universitas Muhammadiyah Kotabumi, 2026)
Rice (Oryza sativa L.) is a primary commodity in stabilizing the food supply of Indonesian people. However, currently the condition of dry land and paddy fields is experiencing land degradation. Land degradation can be restored to fertility using cow dung compost. This study was designed with a two-factor randomized block design (RAK). The first factor is compost consisting of three levels, namely K0 = without compost, K1 = 50% compost dose, K2 = 100% compost. The second factor consists of two levels, namely S0 = without jajar legowo, S1 = jajar legowo 2:1, resulting in six experimental combinations repeated three times, resulting in a total of 18 experimental units. The research results were tested using analysisi of variance (ANOVA) ά = 5%, followed by the least significant difference (LSD) test at the ά = 5% level. Observation variables included plant height (cm), number of productive tillers, number of full grains (per panicle), wet grain yield per plot (kg), and weight of 1,000 dry grains harvested. The results showed that the 2:1 jajar legowo compost system had no impact on plant height or tiller number at 25 days after planting. The application of compost using the 2:1 jajar legowo system significantly affected rice plant height and tiller number at 50 and 70 days after planting. There was an interaction between compost application and the jajar legowo system on rice plant height at MSP. The compost treatment using the 2:1 jajar legowo system significantly affected the weight of 1,000 grains and the harvest weight of the rice.